2022
DOI: 10.1136/ard-2022-222501
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose interleukin-2 therapy in active systemic lupus erythematosus (LUPIL-2): a multicentre, double-blind, randomised and placebo-controlled phase II trial

Abstract: ObjectivesA regulatory T cell (Treg) insufficiency due to shortage of interleukin-2 (IL-2) is central to the pathophysiology of systemic lupus erythematosus (SLE). We performed a multicentre, double-blinded, randomised, placebo-controlled phase II proof-of-concept trial to evaluate the efficacy of low-dose IL-2 therapy in patients with SLE having moderate-to-severe disease activity while receiving standard treatment.MethodsWe randomly assigned 100 patients in a 1:1 ratio to receive either 1.5 million IU/day of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 34 publications
0
40
1
Order By: Relevance
“…Indeed, it was shown in murine and later also in human SLE that an acquired and progressive deficiency of the cytokine interleukin-2 (IL-2), an essential growth and survival factor for Treg, promotes an imbalance between Treg and effector/memory CD4 + T cells, which was associated with accelerated disease activity ( 16 18 ). These pathophysiological findings have stimulated the successful translation of low-dose IL-2 therapy into clinical trials aiming to restore Treg activity in patients with active SLE ( 19 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was shown in murine and later also in human SLE that an acquired and progressive deficiency of the cytokine interleukin-2 (IL-2), an essential growth and survival factor for Treg, promotes an imbalance between Treg and effector/memory CD4 + T cells, which was associated with accelerated disease activity ( 16 18 ). These pathophysiological findings have stimulated the successful translation of low-dose IL-2 therapy into clinical trials aiming to restore Treg activity in patients with active SLE ( 19 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of much lower doses of interleukin-2 (IL-2) than employed in cancer therapy has shown clinical efficacy in a number of inflammatory and autoimmune conditions, by stimulating a subset of CD4 + T cells expressing high levels of the high-affinity trimeric IL-2 receptor, designated as regulatory T (Treg) cells [1][2][3][4][5][6][7][8][9][10][11] . In the autoimmune disease type 1 diabetes (T1D), the genetic association with the IL-2 pathway in mice 12 and in humans 13,14 , combined with preclinical studies 15,16 , have provided a strong rationale for the development of low-dose (LD)-IL-2 immunotherapy.…”
mentioning
confidence: 99%
“…Our study shows large heterogeneity across patients with some with a predominantly Th1 profile, others a Th17 profile, or a Th1-like Th17 profile, while others are mainly characterised by a low IL-2 + Treg profile. As an example, stratifying patients by their IL-2 + Treg titres may dictate response to low-dose IL-2 therapy, as has now been successfully trialled in lupus [42] and RA [43]. Furthermore, a Japanese group found that stratified medicine for psoriatic arthritis patients increased response rates significantly [16].…”
Section: Discussionmentioning
confidence: 99%